2022
DOI: 10.1002/asia.202200762
|View full text |Cite
|
Sign up to set email alerts
|

Selenium‐Electrocatalytic Cyclization of 2‐Vinylanilides towards Indoles of Peptide Labeling

Abstract: A novel selenium‐electrocatalytic intramolecular cyclization of 2‐vinylanilides for synthesis of functionalized indoles and azaindoles has been developed. In contrast to the previous synthetic methods, this sustainable protocol enabled unparalleled broad substrates scope for viable indoles with highly functional and sensitive groups by employing recyclable selenium catalyst, under mild, metal‐ and external‐oxidant‐free conditions. The approach can be used to the late‐stage modification of complex bioactive mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In 2022, Ruan and co-workers [ 36 ] applied electrochemistry to perform the intramolecular cyclisation of 2-vinylanilide 21 using diphenyl diselenide A as a catalyst to synthesise indole 22 . This selenium catalyst protocol has an advantage over indole synthesis 22 since this sustainable method supports several 2-vinylanilide 21 , containing highly functional, sensitive groups and bioactive compounds (natural molecules, drugs, peptides, and amino acid).…”
Section: Application Of Diorganyl Diselenide As a Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Ruan and co-workers [ 36 ] applied electrochemistry to perform the intramolecular cyclisation of 2-vinylanilide 21 using diphenyl diselenide A as a catalyst to synthesise indole 22 . This selenium catalyst protocol has an advantage over indole synthesis 22 since this sustainable method supports several 2-vinylanilide 21 , containing highly functional, sensitive groups and bioactive compounds (natural molecules, drugs, peptides, and amino acid).…”
Section: Application Of Diorganyl Diselenide As a Catalystmentioning
confidence: 99%
“…Similar results were obtained when the starting materials containing drug derivatives were reacted under standard conditions; in these cases, the indoles containing trelagliptin (a drug for type 2 diabetes) portion 22x and lenalidomide (a drug for multiple myeloma) moieties 22y were Scheme 18. Catalyst evaluation for the synthesis of compounds 22a [36].…”
Section: Scheme 18mentioning
confidence: 99%
“…However, there are few reports on electrochemical C‒N bond ring-opening reactions. Within our program on sustainable electrochemical modification of peptides 62 , 63 and cyclic amines 64 , 65 , herein we present an electro-oxidative ring-opening approach to achieve unnatural peptide aldehydes (Fig. 1D ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, organic electrochemistry, employing protons and electrons as redox reagents, has been established as an increasingly powerful and environmentally friendly green tool for the synthesis of functional molecules . Within our own program on electrochemical selenylation and C–H functionalization, herein, we report our first development of an unprecedented protocol for the synthesis of gem -diselenides via electrochemical diselenylation of sulfoxonium ylides with diselenides (Scheme c). Notable features of our approach include (i) the employed substrates are a safer alternative to diazo compounds due to their unique chemical reactivities through C–H carbenoid insertion by transition-metal-catalyzed coupling reactions; (ii) strong base- and metal-free; (iii) undivided cell with mild reaction conditions; (iv) high chemoselectivity toward 1,3-diselenides and good functional group tolerance; (v) mechanistic insights revealed that the oxidation of n- Bu 4 NI as an electrolyte to I 2 in the system promoted the cleavage of the C–H bond and the construction of the C–Se bond; and (vi) monoselenyl-substituted ylides were identified as key intermediates in the electrooxidative transformation.…”
Section: Introductionmentioning
confidence: 99%